From national reforms to local compromises: The evolution of France's model for port management, 2004–2015. (March 2017) - Debrie, Jean; Lacoste, Romuald; Magnan, Marion
Abstract: The French model of port governance has experienced change recently, characterised by two successive reforms that have modified the status of ports. The Law of 13 August 2004 relating to the responsibilities of local authorities (including the devolution of 17 ports of "national interest"), and the reform of seven autonomous ports (given the status of Large Maritime Ports) in 2008 have restructured the evolution of the public organisation of French ports. They have also modified the relationship between port authorities and private operators. The aim of this chapter is to analyse these two reforms and their consequences for port governance. In terms of the devolution of regional ports and the generalisation of the landlord model for major ports, the French model appears to be quite similar to the general trend to devolution of ports throughout the world. Nevertheless, the place of the State (i.e. France's central government) remains important, in the supervision of devolved ports as well as of Large Maritime Ports. Yet, this overall change is transposed variously according to the local context of each port. The transposition of national reforms has led to specific arrangements, so that the port governance model is more complex.